Quality of life of elderly people with gastrointestinal malignant tumors - Wróblewska, Izabela; Wróblewska, Zuzanna; Manulik, Stanisław (Journal of Education, Health and Sport, 2019)
Introduction: Gastrointestinal cancers (GICs) are one of the main factors of morbidity and mortality in the world. They affect the elderly to a large extent, as the natural ageing processes of the human body may also increase the occurrence of pathological changes, which in turn lead to disease. Cancer is now considered a chronic disease that affects the overall functioning of the patient in all areas of the patient's life. For this reason, quality of life (QOL) is more and more often taken into account in the treatment and care of the patient as an important factor influencing further prognosis.Aim: To assess the level of QOL among elderly people with diagnosed GICs.Material and methods: The study included 90 seniors aged >60 years with a diagnosed cancer located in the gastrointestinal tract. The exclusion criteria were: age ˂60, tumors in other part of the body than the gastrointestinal tract, GICs as primary tumor metastasis and dementia. Diagnostic survey method was provided and standardized scales were used to measure QOL: the 30 Items European Organization for Research of Life Questionnaire Core (EORTC QLQ-C30), the 18 Items Esophageal Cancer Module (EORTC QLQ-OES18), the 22 Items Gastric Cancer Module (EORTC QLQ-STO22), and the 29 Items Colorectal Cancer Module (EORTC QLQ-CR29).Results: The QOL of the respondents was assessed as medium (M=54.09; SD=21.91). The analyses showed that age correlates negatively with cognitive (p=0.045) and emotional functioning (p=0.002). Higher QOL was observed among men (M=52.74), economically active people (p=0.027) with a diagnosis up to 6 months (M=49.00) and without stoma was (M=53.07). Respondents define their QOL higher (M=4.00) than the survey results show (M=54.09). The study showed that the youngest seniors (M=2.24), people with liver, pancreas and gallbladder tumors (M=2.89) declared the greatest pain.Conclusions: Reduced QOL in elderly people with GIC is influenced by increased age, female sex, lack of professional activity, long time after the diagnosis of the disease and the presence of the stoma. There are discrepancies between subjective and objective evaluation of QOL, which requires extensive and insightful analysis of QOL, including its components, e.g. pain, in order to improve the seniors’ QOL.